The problem of training party and political staff in dagestan in the 1920s - 1930s - Madina Kurbanismailovna Nagieva (Вестник Майкопского государственного технологического университета, 2023)
The article studies the topical scientific problem of creating the structure of party and political education in the first two decades of the Soviet power. The issues of training qualified personnel for party and state bodies were the most important in the implementation of the national policy of the Soviet state in the specified chronological period. The purpose of the research is to trace the implementation of the policy of training party personnel in the real conditions of the multinational republic of Dagestan. What were the ways and methods of training management personnel? The article highlights the process of political education with the involvement of documentary sources and special scientific research into scientific circulation. The main issues of creating a network of party and political educational institutions in the republic are considered. What were the terms of training, the content and volume of training programs, methods and forms of training? At the initial stage the shortage of personnel was partly made up by organizing courses to train the needed specialists, and after that, creation of training centers. The role of the Soviet party school in personnel training, which began to function in the republic in the 1920s, is especially noted. As a result of the research, the conclusion has been made that thanks to the purposeful work of the Soviet state a system of party education was formed in a short period of time in Dagestan; it worked successfully and its structure consisted of several stages. It included a party school, political schools and courses, circles of the advanced and secondary types, mobile schools, etc. The author concludes that in the 1920s-1930s the foundations of party-political education were laid, which later became one of the important components that influenced the process of forming the leading party cadres.